2011
DOI: 10.1074/jbc.m110.187534
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Factor Aryl Hydrocarbon Receptor (Ahr) Controls Cardiovascular and Respiratory Functions by Regulating the Expression of the Vav3 Proto-oncogene

Abstract: Aryl hydrocarbon receptor (Ahr) is a transcriptional factor involved in detoxification responses to pollutants and in intrinsic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 68 publications
(86 reference statements)
2
34
0
1
Order By: Relevance
“…Consistent with this idea, we have reported previously that the expression of the Vav3 gene, but not that of other Vav family genes, depends on the abundance of the transcription factor Ahr (aryl hydrocarbon receptor) in both mouse tissues and primary cells (36,37). Consistent with this, Vav3 −/− and Ahr −/− mice display similar nervous system and cardiovascular defects (37). Additional experiments will be required to address this issue.…”
Section: Discussionsupporting
confidence: 71%
“…Consistent with this idea, we have reported previously that the expression of the Vav3 gene, but not that of other Vav family genes, depends on the abundance of the transcription factor Ahr (aryl hydrocarbon receptor) in both mouse tissues and primary cells (36,37). Consistent with this, Vav3 −/− and Ahr −/− mice display similar nervous system and cardiovascular defects (37). Additional experiments will be required to address this issue.…”
Section: Discussionsupporting
confidence: 71%
“…Although the functions of Vav proteins in the nervous system are far from clear, several studies have found critical roles for Vav family members in nervous system function. For example, Vav proteins have been shown to be important for axonal development (Cowan et al 2005;Malartre et al 2010;Sauzeau et al 2010a;Fernandez-Espartero et al 2013), synaptic plasticity (Hale et al 2011), and negative regulation of sympathetic nervous system activity (Sauzeau et al 2006(Sauzeau et al , 2007(Sauzeau et al , 2010b(Sauzeau et al , 2011Zhu et al 2015). Moreover, Vav3 has been identified as a candidate schizophrenia gene (Ikeda et al 2011;Aleksic et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic activation of these pathways can cause severe damage to organisms and their ecosystem by altering reproduction, hormonal and/or circulatory systems [73][74][75] as well as they have been associated with carcinogenic and mutagenic effects [76][77][78]. Biological assays allow to complete sunscreens degradation analysis by measuring biological activity of the whole sample taking into account unknown metabolites and potential synergistic effects.…”
Section: Biological Activity Evolution Profile Through the Biodegradamentioning
confidence: 99%